Predictors of poor follow-up after bariatric surgery - BELO,GISELLE DE QUEIROZ MENEZES BATISTA (2018)
ABSTRACT Objective: to identify predictive factors of loss of follow-up of patients submitted to Roux-en-Y gastric bypass and sleeve gastrectomy in a 48-month period. Methods: we conducted a retrospective, cohort study from January 2010 to December 2012. We analyzed thirteen variables and compared them to loss of follow-up. Results: among the 559 patients studied, there was a great reduction in the frequency (43.8%) of the consultations from the second postoperative year on, with a significant loss in the 4th year (70.8%). In the univariate analysis, only the variable “excess weight” was associated with loss of follow-up. The proportion of overweight (>49.95kg) was higher in the follow-up group with greater loss (>3 absences) (p=0.025). In the logistic regression, patients exposed to a greater excess weight (>49.95kg) presented a two-fold higher risk for loss of follow-up (>3 absences) (OR=2.04, 95% CI 1.15-3.62; p=0.015). In the univariate analysis, at the 48th postoperative month, only the variable “mesoregion of origin” was associated with loss of follow-up (p=0.012). Conclusion: there was a progressive loss of follow-up from the second postoperative year on. Among the factors analyzed, only the variable “excess weight” greater than 49.95kg in the preoperative period was associated with loss of medical-surgical follow-up. In the 48th month of the postoperative period, there was a higher prevalence of loss of medical-surgical follow-up for patients outside the perimeter of the city of Recife (51%, p=0.052).